Arthroscopic Caudal Cruciate Ligament Damage in Canine Stifles with Cranial Cruciate Ligament Disease - Agnello, Kimberly A.; Brown, Dorothy Cimino; Zyla, Samuel G.; Hayashi, Kei (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to describe the arthroscopic changes to the caudal cruciate ligament (CdCL) in dogs with cranial cruciate ligament disease.Study Design Arthroscopic video recordings (n = 117) of the stifle with cranial cruciate ligament disease were reviewed. The extent of CdCL tearing was described. Signalment, palpable stifle stability and the presence of a meniscal tear were recorded. Pathology of the synovial joint and the synovium overlying the CdCL were scored at two time points.Two-way interactions were investigated (p < 0.05). Univariate analysis and a Wald test (p < 0.20) were performed. Factors were retained with a Wald test p < 0.05 or if a confounder, then a changing model coefficient >15%. A weighted kappa statistic was used to evaluate intraobserver agreement.Results Caudal cruciate ligament tearing was identified in 94% of stifles. Longitudinal tearing (76%) was the most common type of damage (45% partial, 31% full thickness). Synovitis was present in all joints and changes to the synovium overlying the CdCL were less frequently identified (67%).Synovitis was associated with the degree to CdCL tearing. Synovitis overlying the CdCL was associated with lower body weight and lower CdCL damage.Conclusion Caudal cruciate ligament damage is common in dogs with cranial cruciate ligament disease and longitudinal tearing was the most common injury identified. Severity of joint pouch synovitis was positively correlated with the degree of CdCL damage and the portion of the CdCL not exposed to the synovium was unaffected. These findings suggest synovitis is likely a contributor to CdCL injury.
Keywords: canine; arthroscopy; stifle; caudal cruciate; cranial cruciate